Separated State Assets in BPI Danantara and Its Relevance with Business Judgment Rules - SantosaAnak Agung Gede Duwira Hadi Santosa, Anak Agung Gede Duwira Hadi Santosa; I Made Sarjana, I Made Sarjana; I Made Marta Wijaya, I Made Marta Wijaya; Carmelita Vondra Wijaya, Carmelita Vondra Wijaya (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
The Law Number 1 Year 2025 on the Third Change of Law Number 19 Year 2003 on State-Owned Enterprise (“Amended SOE Law”) became the legal foundation of BPI Danantara’s birth. Being Indonesia’s new Sovereign Wealth Fund to boost national economic performance and public welfare, BPI Danantara carries strategic importance, especially in consolidating SOE dividends and State assets investments. However, the fund’s dual legal character which is public in ownership but private in operational structure raises serious questions about asset status, liability, and governance. This paper found that separated state assets in BPI Danantara constitute state finances, and the Business Judgment Rule (BJR) is not a suitable framework for managing these assets. Even if legal protections such as the BJR are in place, a lack of structural safeguards and transparency mechanisms can undermine investor confidence and trigger legal disputes. To address the norm conflict, this paper proposes a two-pronged approach under a normative legal method: (1) legislative clarification on the status of separated state assets under both finance and corporate law; and (2) codified governance mechanisms that ensure oversight without stifling legitimate business risk-taking. Such reforms would offer BPI Danantara directors the confidence to act decisively under BJR while ensuring accountability standards expected of stewards of public wealth.